Ethical considerations in biomedical HIV prevention trials (UNAIDS, 2007)
Well into the third decade of the HIV epidemic, there remains no effective HIV preventive vaccine, microbicide, product or drug to reduce the risk of HIV acquisition. As the numbers of those infected by HIV and dying from AIDS continue to increase, the need for such biomedical HIV preventive interventions becomes ever more urgent. Several such products are at various stages of development, including some currently in phase III efficacy trials. The successful development of effective HIV preventive interventions requires that many different candidates be studied simultaneously in different populations around the world.